Insurance Value of International Reserves : An Option Pricing Approach - Lee, Jaewoo (IMF Working Papers; Working Paper ;, 2004)
A quantitative framework is developed to bring forward the insurance motive of holding international reserves. The insurance value of reserves is quantified as the market price of an equivalent option that provides the same insurance coverage as the reserves. This quantitative framework is applied to calculating the cost of a regional insurance arrangement (e.g., an Asian Monetary Fund) and to analyzing one leg of an optimal reserve-holding decision.